An LC-MS/MS method for the determination of 28 polar environmental contaminants and metabolites in vegetables irrigated with treated municipal wastewater. Issue 8 (10th February 2017) - Riemenschneider, Christina; Seiwert, Bettina; Goldstein, Myah; Al-Raggad, Marwan; Salameh, Elias; Chefetz, Benny; Reemtsma, Thorsten
Abstract : An analytical method for the determination of wastewater-derived contaminants and possible metabolites in common plant tissues was developed and validated. Abstract : An analytical method for the simultaneous determination of 28 wastewater-derived contaminants and possible metabolites ( e.g. carbamazepine, 10, 11-epoxy-carbamazepine, benzotriazole, lamotrigine, and diclofenac) in common plant tissues with high water content (lettuce, cabbage, and tomato) was developed and validated. The developed method combines solid–liquid extraction, without the need for a clean-up step, and liquid chromatography-tandem mass spectrometry (LC-MS/MS) with electrospray ionization in positive and negative modes. This method was compared with the known QuEChERS method and exhibited better analytical performance. Method detection limits of ≤2.0 ng g −1 dry weight and absolute recoveries of >60% with high intra- and inter-day precision (RSD < 10%) could be achieved for 71% of the target analytes in four different matrices (cabbage, lettuce and tomato leaves, and tomato fruits). Compared to the QuEChERS method, the developed method allows the determination of a wide range of compounds with different physical–chemical properties (neutral, acidic, and basic) and considers even possible metabolites of pharmaceuticals in plant materials. The developed method was successfully applied to analyse wastewater-derived contaminants and their metabolites in plants which were grown under greenhouse and real field conditions. It could be shown that this method is suitable for the sensitive determination of environmental contaminants originating from treated wastewater and a range of their metabolites in irrigated plants and their edible parts. Due to its broadness the extraction method should also be suitable for screening of unknown contaminants and metabolites by LC high-resolution mass spectrometry.